Agglomeration, congestion, and regional unemployment disparities - Ulrich Zierahn (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2011)
Regional labor markets are characterized by huge disparities between unemployment rates. Models of the New Economic Geography explain how disparities between regional goods markets endogenously arise but usually assume full employment. This paper discusses regional unemployment disparities by introducing a wage curve based on efficiency wages into the New Economic Geography. The model shows how disparities between regional goods and labor markets endogenously arise through the interplay of increasing returns to scale, transport costs, congestion costs, and migration. The level and stability of regional labor market disparities depends on the extend of labor market frictions.
Keywords: J64; R12; R23; 330; regional unemployment; New Economic Geography; core-periphery; wage curve; labor migration